Charge-induced structural transition between seashell-like B29− and B29+ in 18 π-electron configurations. Issue 22 (24th May 2018) - Pei, Ling; Li, Hai-Ru; Yan, Miao; Chen, Qiang; Mu, Yue-Wen; Lu, Hai-Gang; Wu, Yan-Bo; Li, Si-Dian
Abstract : First-principles theory investigations show a clear charge-induced structural transition between seashell-like C s B29 − (1 − ) and C s B29 + (1 + ) in 18 π-electron configurations. Abstract : Recent joint experimental and theoretical investigations have shown that seashell-like C 2 B28 is the smallest neutral borospherene reported to date, while seashell-like C s B29 − (1 − ) as a minor isomer competes with its quasi-planar counterparts in B29 − cluster beams. Extensive global minimum searches and first-principles theory calculations performed in this work indicate that with two valence electrons detached from B29 −, the B29 + monocation favors a seashell-like C s B29 + (1 + ) much different from C s B29 − (1 − ) in geometry which is overwhelmingly the global minimum of the system with three B7 heptagonal holes in the front, on the back, and at the bottom, respectively, unveiling an interesting charge-induced structural transition from C s B29 − (1 − ) to C s B29 + (1 + ). Detailed bonding analyses show that with one less σ bond than B29 − (1 − ), C s B29 + (1 + ) also possesses nine delocalized π-bonds over its σ-skeleton on the cage surface with a σ + π double delocalization bonding pattern and follows the 2( n + 1) 2 electron counting rule for 3D spherical aromaticity ( n = 2). B29 + (1 + ) is therefore the smallest borospherene monocation reported to date which is π-isovalent with the smallest neutral borospherene C 2 B28 . The IR, Raman, and UV-vis spectra of B29 + (1 + ) are computationally simulated to facilitate its spectroscopic characterization.